2022
DOI: 10.1002/advs.202204998
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Fibroblast‐Like Synoviocytes Cell Membrane Coated Nanoparticles: A Novel Targeted Therapy for Rheumatoid Arthritis

Abstract: Fibroblast-like synoviocytes (FLS) are the main cell component in the inflamed joints of patients with rheumatoid arthritis (RA). FLS intimately interact with infiltrating T cells. Fibroblasts have potent inhibitory effects on T cells, leading to the resolution of inflammation and immune tolerance. However, this "regulatory" phenotype is defect in RA, and FLS in RA instead act as "proinflammatory" phenotype mediating inflammation perpetuation. Signals that orchestrate fibroblast heterogeneity remain unclear. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…Cytotoxicity and Hemolysis Assay: RAW 264.7 and MH7A cells were cultured in 96 well plates at a density of 1 × 10 4 per well and incubated with Leo@CAT@NM-Lipo at different concentrations (1,10,20,50,100,200,500, and 1000 μg mL −1 ), or incubated with Leo, Leo@CAT@Lipo and Leo@CAT@NM-Lipo (equivalent Leo dose at 10 μM) at 37 °C for 24 h. Afterward, each well was rinsed gently with PBS, replenished with 90 μL of fresh medium and 10 μL of CCK-8, and incubated for another 4 h at 37 °C. The absorbance of each well was measured at 450 nm by a microplate reader (SpectraMax ID5, Molecule Devices, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxicity and Hemolysis Assay: RAW 264.7 and MH7A cells were cultured in 96 well plates at a density of 1 × 10 4 per well and incubated with Leo@CAT@NM-Lipo at different concentrations (1,10,20,50,100,200,500, and 1000 μg mL −1 ), or incubated with Leo, Leo@CAT@Lipo and Leo@CAT@NM-Lipo (equivalent Leo dose at 10 μM) at 37 °C for 24 h. Afterward, each well was rinsed gently with PBS, replenished with 90 μL of fresh medium and 10 μL of CCK-8, and incubated for another 4 h at 37 °C. The absorbance of each well was measured at 450 nm by a microplate reader (SpectraMax ID5, Molecule Devices, USA).…”
Section: Methodsmentioning
confidence: 99%
“…[19] So far, FLS, leukocytes, platelets, erythrocytes, or their combinations have been adopted for biomimetic nanomedicine construction targeting RA treatments. [20] Among them, neutrophils are the first responders to inflammation and infiltrate into the cartilage-pannus junction by intimate interactions between the upregulated adhesion molecules, overexpressed cytokines, and excessive chemokines in the lesion and the membrane antigens of neutrophils. [21] Subsequently, the recruited neutrophils further release proinflammatory cytokines, proteases, ROS, chemokines, and neutrophil extracellular traps (NETs) to aggravate joint degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinspired vesicle-based nanoparticles have shown potential in organ-specific RNA delivery while decreasing toxicity. These nanoparticles consist of biological elements, such as extracellular vehicles (EVs) and liposomes, mimicking the processes of biological systems. EVs, which are membrane-coated nanoparticles, are derived from prokaryotic and eukaryotic cells and can carry RNA, proteins, lipids, and DNA. The application of EVs as delivery vehicles for RNA and other biological molecules shows promise in preventing degradation in vivo and delivering them to targeted cells without immune activation.…”
Section: Chemical Modifications On Rna Nanodelivery Platformsmentioning
confidence: 99%
“…Similarly, our study showed that FLSs stimulated by IFN-γ can upregulate the expression of several inhibitory molecules, such as PD-L1 and galectin-9, on the cell membrane, which might be negative feedback mechanisms of inflammatory cytokines. FLS cell membranes with high expression of inhibitory molecules ameliorated inflammation and bone damage in CIA [ 76 ]. These data suggest that the introduction of fibroblasts with immunosuppressive/pro-resolving effects may help restore the balance of FLS subsets.…”
Section: Strategies For Targeting Pathogenic Fls Subsets In Ramentioning
confidence: 99%